2021
DOI: 10.3390/ijms22179618
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Effects of Mineralocorticoid Pathway Activation in Retinal Pigment Epithelium

Abstract: Glucocorticoids are amongst the most used drugs to treat retinal diseases of various origins. Yet, the transcriptional regulations induced by glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) activation in retinal pigment epithelium cells (RPE) that form the outer blood–retina barrier are unknown. Levels of endogenous corticoids, ligands for MR and GR, were measured in human ocular media. Human RPE cells derived from induced pluripotent stem cells (iRPE) were used to analyze the pan-transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 61 publications
(72 reference statements)
1
17
1
Order By: Relevance
“…The MR immunohistochemistry images shown in this paper supports that MR might have been degraded since the MR signal in the retina is extremely low, without any signal in ganglion cells, in retinal endothelial cells and very scarce signal in few cells the inner retina, which is very different with what has been found by several other authors (2-4). There is no MR signal in the nuclei of any cells in the choroid and no MR signal in the nuclei of retinal pigment epithelial cells either, which is very different from previous results obtained on fresh tissues and cells (5,6). More importantly, the positive MR control do not show any signal in the nuclei, which could indicate methodological issues.…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…The MR immunohistochemistry images shown in this paper supports that MR might have been degraded since the MR signal in the retina is extremely low, without any signal in ganglion cells, in retinal endothelial cells and very scarce signal in few cells the inner retina, which is very different with what has been found by several other authors (2-4). There is no MR signal in the nuclei of any cells in the choroid and no MR signal in the nuclei of retinal pigment epithelial cells either, which is very different from previous results obtained on fresh tissues and cells (5,6). More importantly, the positive MR control do not show any signal in the nuclei, which could indicate methodological issues.…”
contrasting
confidence: 90%
“…The authors claim that there is no animal model that recapitulate human pachychoroid phenotype but they omitted to cite the P1hMR mouse model (mouse that overexpresses human MR) (6) and the NAS (nephrectomy aldosterone salt) models ( 7) that show all features of human eyes with pachychoroid.…”
mentioning
confidence: 99%
“…In our experiments, we never detected any aldosterone in the retina nor in the ocular media from rodents and humans, using either radioimmunoassay or highly sensitive MS techniques (Canonica et al, 2019; Zhao et al, 2021). Previous results also indicated that the human retinal pigment epithelium cell line, ARPE19, could produce and secrete cortisol (Zmijewski et al, 2007), but using native human retinal pigment epithelium cells and human retinal pigment epithelium cells derived from induced pluripotent stem (iPS) cells, we have not been able to reproduce this result nor to show that retinal pigment epithelium could produce either cortisol or aldosterone (Canonica et al, 2021).…”
Section: Mineralocorticoid and Glucocorticoid Receptors: Their Ligand...mentioning
confidence: 67%
“…We recently described the retinal phenotype of these mice (provided by Marc Lombes, Damien Le Menuet and Say Viengchareun). Interestingly, enlarged choroidal vessels, choroidal excavations, disorganization of the Bruch membrane and pigments in retinal pigment epithelium cells, focal retinal pigment epithelium proliferation and elongation of photoreceptor outer segments (Canonica et al, 2021) (Figure 3d) resemble human pachychoroid pigment epitheliopathy (Figure 3e).…”
Section: Consequences Of Experimental Mineralocorticoid Receptor Path...mentioning
confidence: 99%
“…In RPE/ choroid complex, we quantified the expression of genes shown to be upregulated by aldosterone or MR pathway activation in human RPE cells derives from iPS such as Plaur encoding the urokinase plasminogen activator receptor (uPAR) and Fosl1 encoding the FOS like 1 AP-1 transcription factor subunit protein, Ptx3 encoding pentraxin 3 and Omg that encodes the oligodendrocyte myelin glycoprotein and that was down-regulated by aldosterone or Cortisol+ RU486 [65]. We also tested genes showed to be upregulated in the RPE/choroid complex after intravitreal injection of aldosterone such as Ngal encoding lipocalin 2 and Mmp9 and the Shroom Family Member 2 Shroom2, that is implicated in amiloride-sensitive sodium channel activity [66].…”
Section: Quantitative Pcrmentioning
confidence: 99%